MTOR-sensitive translation: Cleared fog reveals more trees. Issue 10 (3rd October 2017) - Masvidal, Laia; Hulea, Laura; Furic, Luc; Topisirovic, Ivan; Larsson, Ola
ABSTRACT: Translation is fundamental for many biologic processes as it enables cells to rapidly respond to stimuli without requiring de novo mRNA synthesis. The mammalian/mechanistic target of rapamycin (mTOR) is a key regulator of translation. Although mTOR affects global protein synthesis, translation of a subset of mRNAs appears to be exceptionally sensitive to changes in mTOR activity. Recent efforts to catalog these mTOR-sensitive mRNAs resulted in conflicting results. Whereas ribosome-profiling almost exclusively identified 5′-terminal oligopyrimidine (TOP) mRNAs as mTOR-sensitive, polysome-profiling suggested that mTOR also regulates translation of non-TOP mRNAs. This inconsistency was explained by analytical and technical biases limiting the efficiency of ribosome-profiling in detecting mRNAs showing differential translation. Moreover, genome-wide characterization of 5′UTRs of non-TOP mTOR-sensitive mRNAs revealed 2 subsets of transcripts which differ in their requirement for translation initiation factors and biologic functions. We summarize these recent advances and their impact on the understanding of mTOR-sensitive translation.